Bioactivity of Ionic Liquids Based on Valproate in SH-SY5Y Human Neuroblastoma Cell Line - Noronha, João Paulo da Costa de (2022)
This work received financial support from the PT national funds (FCT-MCTES, Fundação para a Ciência e Tecnologia and Ministério da Ciência, Tecnologia e Ensino Superior) through the project UIDB/50006/2020 | UIDP/50006/2020. A.F.M.S. and Ž.P. also acknowledge FCT-MCTES for the PhD grant (SFRH/BD/132551/2017) and Norma Transitória DL 57/2016 program contract, respectively